Lobi dan Negosiasi sebagai Strategi Komunikasi Efektif dalam Membangun Kesepakatan di Ranah Organisasi dan Kebijakan Publik - Sabrina Puspita Sari; Chitra Cahya Anggraeni; Noviatul Fitri; Gandhes Lintang Pangestu; Putria Nuraliza Rochman (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Lobbying and negotiation are two vital communication strategies in decision-making processes, both within organizational and public policy domains. This study aims to examine how lobbying and negotiation practices function as strategic communication tools to enhance the effectiveness of stakeholder relationships. The study presents 20 citations from scholarly journal articles as the basis for analysis. A descriptive qualitative literature study method was used. The findings indicate that both lobbying and negotiation contribute to the creation of more inclusive, efficient, and adaptive decisions in strategic environments.